A COMPARATIVE ANALYSIS OF ENGLISH AND UZBEK IDIOMS: CULTURAL EXPRESSIONS THROUGH LANGUAGE - Kokanova Nursuliu Jenisbay qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Idioms are fascinating linguistic phenomena that provide insight into the cultural and social fabric of a language. This scientific article explores the similarities and differences between English and Uzbek idioms, shedding light on the unique ways in which these languages express cultural concepts. Through a comparative analysis, we examine the origins, structure, and semantic nuances of idiomatic expressions in both languages. The findings not only enhance our understanding of language diversity but also foster intercultural communication and appreciation.